Covid- 19 Pandemic And Its Impact On The Lecturers’ And Students’ Performance In Teaching And Learning At Kenyatta University, Kenya - Kombo, Kisilu; Itumo, Joshua M. (Machakos University Press, 2022)
The outbreak of the Covid-19 pandemic brought unprecedented disruptions in all aspects of human life across the globe. In the education sector, university calendars were re-scheduled and in-class learning was commuted to online platforms. The present study focused on performance of lecturers and students at Kenyatta University. The chosen institution has the second largest number of enrolled students and it is ranked as number 2 in Kenya. Performance, in this study, is broadly defined as ‘the expectations placed on the lecturers and students during their stay at the University’. Performance during the post-Covid period has received little attention in literature relating to adjustments in universities. A case study approach was adopted within the broad mixed-methods research design. Interviews and questionnaires were used to obtain qualitative data. Quantitative data derived from questionnaires was computed into mean and Standard Deviation scores. This was further subjected to Analysis of Variance (ANOVA) using the Statistical Package for the Social Sciences (SPSS). The Pearson-mark was also used to correlate the data. The findings indicated that interactive activities were drastically reduced during the post- Covid period; a significant number of classes and postgraduate defenses were postponed for various reasons. Make-up classes were created from time to time; reduced class attendance; failure by students to remain in classes throughout the entire class sessions; internet interruptions and numerous disconnections were reported. Modules were written as a stopgap measure for augmenting lost time. The paradigm shifts in pedagogical approaches impeded, to some extent, the lecturers and students’ performance. Activities on proposal writing for funding and research activities were drastically reduced. In conclusion, the University lost heavily due the intermittent resurgence of the pandemic and a sluggish approach to confront it. The study recommends a robust online-based system of monitoring classes and postgraduate defenses; provision of internet for both students and lecturers in order to avoid numerous disconnections. Lastly, both students and lecturers should be proactive in order to surmount the Covid-19 related challenges.
Keywords: Performance; E-trinities; Monitoring; Challenges; Interactions; Disruptions